Autophagy genes AMBRA1 and ATG8 play key roles in midgut remodeling of the yellow fever mosquito, Aedes aegypti - Albishi, Najla M.; Palli, Subba Reddy (Frontiers in Insect Science, 2023)
The function of two autophagy genes, an activating molecule BECN1 regulated autophagy (AMBRA1) and autophagy-related gene 8 (ATG8) in the midgut remodeling of Ae. Aegypti was investigated. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis of RNA samples collected from the last instar larvae and pupae showed that these two genes are predominantly expressed during the last 12 h and first 24 h of the last larval and pupal stages, respectively. Stable ecdysteroid analog induced and juvenile hormone (JH) analog suppressed these genes. RNA interference (RNAi) studies showed that the ecdysone-induced transcription factor E93 is required for the expression of these genes. JH-induced transcription factor krüppel homolog 1 (Kr-h1) suppressed the expression of these genes. RNAi-mediated silencing of AMBRA1 and ATG8 blocked midgut remodeling. Histological studies of midguts from insects at 48 h after ecdysis to the final larval stage and 12 h after ecdysis to the pupal stage showed that ATG gene knockdown blocked midgut remodeling. AMBRA1 and ATG8 double-stranded (dsRNA)-treated insects retained larval midgut cells and died during the pupal stage. Together, these results demonstrate that ecdysteroid induction of ATG genes initiates autophagy programmed cell death during midgut remodeling. JH inhibits midgut remodeling during metamorphosis by interfering with the expression of ATG genes.